EPHA2 MUTATIONS CONTRIBUTE TO CONGENITAL CATARACT THROUGH DIVERSE MECHANISMS - Dave, Alpana (Mol Vis, 2016)
PURPOSE: Congenital cataract is a leading cause of childhood blindness. Mutations in the EPHA2 gene are one of the causes of inherited congenital cataract. The EPHA2 gene encodes a membrane-bound tyrosine kinase receptor and is highly expressed in epithelial cells, including in the ocular lens. Signaling through the EPHA2 receptor plays a pivotal role in epithelial cell homeostasis. The aim of this study was to determine the effect of congenital cataract causing mutations in the EPHA2 gene on the encoded protein in epithelial cells. METHODS: The effect of five disease-causing mutations, p.P584L (c.1751C>T), p.T940I (c.2819C>T), p.D942fsXC71 (c.2826–9G>A), p.A959T (c.2875G>A), and p.V972GfsX39 (c.2915_2916delTG), on localization of the protein was examined in two in vitro epithelial cell culture systems: Madin-Darby Canine Kidney (MDCK) and human colorectal adenocarcinoma (Caco-2) epithelial cells. Myc-tagged mutant constructs were generated by polymerase chain reaction (PCR)-based mutagenesis. The Myc-tagged wild-type construct was used as a control. The Myc-tagged wild-type and mutant proteins were ectopically expressed and detected by immunofluorescence labeling. RESULTS: Two of the mutations, p.T940I and p.D942fsXC71, located within the cytoplasmic sterile-α-motif (SAM) domain of EPHA2, led to mis-localization of the protein to the perinuclear space and co-localization with the cis-golgi apparatus, indicating sub-organellar/cellular retention of the mutant proteins. The mutant proteins carrying the remaining three mutations, similar to the wild-type EPHA2, localized to the cell membrane. CONCLUSIONS: Mis-localization of two of the mutant proteins in epithelial cells suggests that some disease-causing mutations in EPHA2 likely affect lens epithelial cell homeostasis and contribute to cataract. This study suggests that mutations in EPHA2 contribute to congenital cataract through diverse mechanisms.